Effects of solution pH and processing cycle on nanostructured La 2(MoO 4) 3 produced by cyclic microwave radiation - Keereeta Y. (2014)
La 2(MoO 4) 3 with different morphologies were successfully produced by a facile cyclic microwave radiation (CMR) processing of a 2:3 molar ratio lanthanum to molybdenum of La(NO 3) 3·6H 2O and (NH 4) 6Mo 7O 24·4H 2O in the solutions with different pH values adjusted by 2 M NaOH for different processing cycles. XRD, SEM, TEM, HRTEM and SAED showed that La 2(MoO 4) 3 microflowers of nanoflake-like petals could be produced by a 180 W CMR for 15 cycles in the solutions with the pH 7 and 8. The 904 and 887 cm -1 Raman symmetric stretching modes as well as the 320 cm -1 asymmetric bending modes were detected, and direct energy gaps of the UV-visible spectroscopy were 3.47 and 3.85 eV, respectively. The formation mechanism was also proposed in relation to the experimental results. © 2012 Elsevier B.V. All rights reserved.